ARAHAN PENGGUNAAN LAHAN DENGAN METODE SKORING PADA SUB DAS UNDA HULU (RECOMMENDED LAND USE PATTERN BY SCORING METHOD AT UNDA WATERSHED) - -, WIYANTI (AGRITROP; Vol. 29, No. 4 Desember 2010)
Research has been conducted at Unda watershed. The aim of this experiment is to determine the land use pattern of Unda watershed. A method used in this research was by scoring which is introduced by Bambang Sukartiko. In this method, three factors has been considered such as : slope of land, soil type based on susceptibility to erosion, and daily rain intensity. Land unit has been determined with the compilation of maps of slope, soil type and land use. It was 32 land units has been determined. Based on the result of research, it was found that Unda watershed especially in forest area recommended the land use pattern was forest production and conservation forest. Meanwhile, in outer area, it was focused to be a plantation of perennial and annual crops, as well as a buffer zone. The forest production was found at land unit number of 9, 10, 11 and the conservation forest at land unit number 12. The annual plantation was found at land unit number 1, 5 and 6; while perennial crops was in land unit number 4 , 23, 24, 28 and 29. The buffer zone was in land unit number 2, 3, 7, 8, 13, 15,16, 17, 18, 19, 20, 21, 22, 25, 26, 27, 30, 31 32.
Keywords: Land use pattern, watershed, scoring method